Decomposing the Labor Market Earnings Inequality: The Public and Private Sectors in Vietnam, 1993-2006 - Imbert, Clément (World Bank, Washington, DC, 2013)
In contrast with the typical transition to a market economy, earnings inequality in Vietnam between 1993 and 2006 appears to have decreased, and the earnings gap in favor of public employees appears to have widened. The paper uses a comparative advantage model to disentangle the effect of sorting workers across sectors from the effect of the differences in returns to workers' skills. The selection of the best workers into the public sector is clearly an important component of the explanation for the public-private sector earnings gap, but the widening of this gap over time is primarily due to changes in the compensation patterns. The paper finds that, in the 1990s, public employees were underpaid compared with their earning potential in the private sector whereas, in the early 2000s, public employees earned similar returns to their comparative advantage in the public and private sectors. The increasing homogeneity in returns to skills in the Vietnamese labor market appears to explain both the increase in the public-private pay gap and the decrease in overall inequality.